So-called autistic children in school: repercussions of research in the master in teaching - Rodrigues, Maria Goretti Andrade; Sousa, Renata Domingues Gonçalves Caveari de; Vargas, Thamyres Bandoli Tavares (Universidad Pedagógica y Tecnológica de Colombia, 2019)
We propose in this article to think of lines of flight from the usual positions on children, in order to achieve a philosophical thinking able to open space for new possibilities with the so-called autistic children in the school, from the results of research in the Master’s Degree in Teaching of the Federal Fluminense University. We rescued the nomenclatures attributed to the students in the situation of inclusion.We focused on the abnormal, from Foucault’s point of view, in order to achieve a displacement of the teacher’s perspective of estrangement in the school on the childhood that resists to concentric and totalizing movements. We use cartography as a methodological course, where research and intervention cannot be unlinked. We understand that writing is not the result of research, but it is research itself.